2022
DOI: 10.1038/s41392-022-01182-w
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule inhibitor of the UBE2F-CRL5 axis induces apoptosis and radiosensitization in lung cancer

Abstract: Protein neddylation is catalyzed by a neddylation activating enzyme (NAE, E1), an E2 conjugating enzyme, and an E3 ligase. In various types of human cancers, the neddylation pathway is abnormally activated. Our previous study validated that the neddylation E2 UBE2F is a promising therapeutic target in lung cancer. Although the NAE inhibitor MLN4924/pevonedistat is currently under clinical investigation as an anti-cancer agent, there are no small molecules available that selectively target UBE2F. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…HA-9104 interacts with UBE2F to reduce its protein levels (via a yet-to-defined mechanism), thereby inhibiting CUL5 neddylation. Blockage of CUL5 neddylation results in CRL5 inhibition and NOXA accumulation to trigger apoptosis [ 48 ]. Since UBE2F inhibition promotes apoptosis and suppresses cancer cell growth (Fig.…”
Section: Ube2f Inhibition Induces Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…HA-9104 interacts with UBE2F to reduce its protein levels (via a yet-to-defined mechanism), thereby inhibiting CUL5 neddylation. Blockage of CUL5 neddylation results in CRL5 inhibition and NOXA accumulation to trigger apoptosis [ 48 ]. Since UBE2F inhibition promotes apoptosis and suppresses cancer cell growth (Fig.…”
Section: Ube2f Inhibition Induces Apoptosismentioning
confidence: 99%
“…Nevertheless, the induction of drug-resistant mutations in UBA3 inhibits the formation of the MLN4924-NEDD8 adduct, necessitating the need to explore alternative targets against the neddylation pathway [ 45 , 46 ]. To address the limitations of MLN4924, specific inhibitors against neddylation E2s are being investigated [ 47 , 48 ]. This review summarizes the latest progress on validating the neddylation of these enzymes as promising anti-tumor targets.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Sun's research group, for the first time, reported an azaindole-based UBE2F inhibitor HA-9104, which was obtained through a structure-based virtual screen and multiple rounds of chemistry-based optimization 230 . HA-9104 could effectively bind to UBE2F protein and decrease its expression, resulting in the inhibition of cullin-5 neddylation.…”
Section: Inhibitors Of Neddylation Enzymesmentioning
confidence: 99%
“… [ 38 ] 2 HA-9104 IC 50 = 49 µM a UBE2F Inhibit CULLIN5 neddylation and accumulate CRL5 substrate NOXA [ 77 ] 3 Arctigenin IC 50 < 2.5 µM UBE2M Inhibit CULLIN 1-4 neddylation and accumulate tumor suppressor PDCD4 protein. [ 78 ] 4 NAcM-OPT IC 50 = 80 nM DCN1 Inhibit CULLIN1 and CULLIN3 neddylation in 10 µM in HCC95 cells. [ 79 ] 5 NAcM-COV IC 50 ≤ 40 nM DCN1 Inhibit CULLIN1 and cullin3 neddylation at 10 µM in HCC95 cells.…”
Section: Inhibitors Reported Against E2-based Protein-protein Interac...mentioning
confidence: 99%
“…They demonstrated that HA-1141, a small molecule, can inhibit the collaboration between F56 and NAE [ 38 ]. Later, Tiantian Xu et al described HA-9104, another small molecule capable of inhibiting the interaction between UBE2F and NAE when targeted to the V30 pocket [ 78 ]. In addition, Yi-fan Chen et al conducted cell-based natural product inhibitor screening and observed UBE2M neddylation changes upon inhibitor application.…”
Section: Inhibitors Reported Against E2-based Protein-protein Interac...mentioning
confidence: 99%